EARLY DETECTION AND COMPREHENSIVE THERAPEUTIC APPROACHES IN DIABETES MELLITUS (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses methods for detecting early stages of diabetes, the possibilities of stopping the development of the disease at these stages, and comprehensive treatment approaches. The importance of modern diagnostic tools, clinical symptoms, and laboratory indicators for early diagnosis is analyzed. Also, comprehensive therapy methods, including lifestyle changes, pharmacological agents, psychological support, and physical activity, are discussed. The study substantiates the need to introduce advanced approaches in medical practice.